2009
DOI: 10.1186/1471-2210-9-s2-a55
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of bilberry extract on ischemia-reperfusion-induced injury in isolated rat heart

Abstract: Background Bilberries (Vaccinium myrtillus L.) are recognized as a good source of flavonoids, especially anthocyanins, which have strong antioxidative activity. Therefore, they may have a strong potential as cardioprotective agents in ischemicreperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…mg) during two months could contribute to explain the cardiovascular disease protective role of a diet rich in fruits and vegetables. Žiberna et al [78] observed that the administration of a V. myrtillus extract (0.01-5 mg/L) to rats increased coronary flow up to 2.5-fold, and decreased lactate dehydrogenase (LDH) release rate during reperfusion by 3.7-fold at 0.1 mg/L and by 6.7-fold at 1 mg/L, compared to controls. It was also effective in the prevention of arrhythmias, whose duration was maximally shortened at 0.1 mg/L to 3.2 ± 0.2 %, and at 1 mg/L to 4.4 ± 0.3 %, in relation to the untreated group.…”
Section: Cardioprotective Effectsmentioning
confidence: 99%
“…mg) during two months could contribute to explain the cardiovascular disease protective role of a diet rich in fruits and vegetables. Žiberna et al [78] observed that the administration of a V. myrtillus extract (0.01-5 mg/L) to rats increased coronary flow up to 2.5-fold, and decreased lactate dehydrogenase (LDH) release rate during reperfusion by 3.7-fold at 0.1 mg/L and by 6.7-fold at 1 mg/L, compared to controls. It was also effective in the prevention of arrhythmias, whose duration was maximally shortened at 0.1 mg/L to 3.2 ± 0.2 %, and at 1 mg/L to 4.4 ± 0.3 %, in relation to the untreated group.…”
Section: Cardioprotective Effectsmentioning
confidence: 99%